Information Communication Technology Use for Public Safety in the United States - Kapucu, Naim; Haupt, Brittany (Frontiers in Communication, 2016)
Information communication technology (ICT) is a crucial tool to support effective communication and decision-making under complex and uncertain environments of disasters by enhancing cognitive capacity of emergency managers. With the continuous influence and evolution of communication technologies, information sharing and decision making has drastically changed and affects each phase of emergency management. Researchers continue to investigate the relationship of human involvement for spreading public safety information through ICT. With each disaster holding diverse characteristics influencing prediction, detection, and specific activities required for prevention, mitigation, response and recovery, the need for interoperable and dependable communication infrastructure, a common operating picture, and supportive regulations, policies and practice greatly increases. Although a national public safety communication system was proposed, there are implementation challenges between local, state and federal agencies. This paper briefly examines the evolution of the use of ICT for public safety along with current trends, benefits and challenges, and future needs.